Uargueziz (International Library of African Music, 2015)
The song Uargueziz reflects the message of many other Saharawi nationalist songs of bravery and fighting. Uargueziz is meant to unite and to reinforce the nationalist struggle of the Saharawis. Through songs such as Uargueziz, performers and local audiences are drawn to the same cultural values and national ideology. Thus, political homogeneity between the PF, music makers and their audience in the camps is the main pillar for Saharawi musical expression. Equally noteworthy, is the role of musicians and poets to serve the RASD in this refugee context. For that reason, Uargueziz reaches out to the three different social structures of communicational reciprocity between the PF, Saharawi musicians and the local audience.
Keywords: African Music